Comparative analysis of lipid components in fresh Crassostrea Hongkongensis (raw) and its dried products by using high-performance liquid chromatography/quadrupole time-of-flight mass spectrometry (HPLC/Q-TOF-MS) - Sun, Qunzhao; Wang, Yunru; Cai, Qiuxing; Pang, Tingcai; Lan, Weibing; Li, Laihao (Frontiers in Nutrition, 2023)
Lipids of the oyster (Crassostrea hongkongensis) have a special physiological activity function, which are essential to maintain human health. However, the comprehensive research on their lipids species and metabolism are not so common. In our study, based on the high performance liquid chromatography/quadrupole time-of-flight mass spectrometer (HPLC/Q-TOF-MS), the non-targeted lipidomics research of Crassostrea hongkongensis fresh and dried products were determined. Meanwhile, we analyzed its lipid outline, screened the differences between the lipid molecules of Crassostrea hongkongensis fresh and dried products, and determined the lipid metabolic pathway. Results showed that 1523 lipid molecules were detected, in which polyunsaturated fatty acids mostly existed in such lipids as phosphoglyceride. Through multivariate statistical analysis, according to the conditions of P < 0.05, FC > 2 or FC < 0.05 and VIP > 1.2, 239 different lipid molecules were selected, including 37 fatty acids (FA), 60 glycerol phospholipids (GP), 20 glycerin (GL), 38 sheath lipids (SP), 31 steroid lipids (ST), 36 polyethylene (PK), and 17 progesterone lipids (PR). Combined with the Kyoto Encyclopedia of Genes and Genomes (KEGG), the differential lipid molecules were analyzed to mainly determine the role of glycerin phospholipid metabolic pathway. As a whole, the results of this study provide the theoretical basis for the high-value utilization of oysters, and are helpful to the development of oyster physiological activity functions and deep utilization.